PENINGKATAN AKTIVITAS DAN PEMAHAMAN SISWA DALAM PEMBELAJARAN KIMIA MELALUI PENDEKATAN KONTEKSTUAL - Indarini Dwi Pursitasari (Universitas Negeri Malang, 2016)
The Improvement of Students' Activities and Understanding in Chemistry through Contextual Teaching. This study was conducted in order to improve the students' activities as well as the learning outcomes in the subject of thermochemistry through contextual teaching. The subjects of the study were 21 students of Grade XI IPA 2 of Madrasah Aliyah Alhaerat Palu. Observations as well as reflection were carried out during the treatment process. Questionnaire was distributed after the treatment was given. The study revealed that contextual teaching was successful in improving the students' activities and learning outcomes.